The Effectiveness of Football Pass Learning Models Through the Peer Tutor - Reza Resah Pratama; Topo Yono (JIPES - JOURNAL OF INDONESIAN PHYSICAL EDUCATION AND SPORT, 2023)
The purpose of this study was to determine the effectiveness of the learning model that has been developed in football passing material. The learning model with the peer tutor approach is used as a form of variation in delivering learning material to students. Thirty-two Junior High School students in Palembang became the research object of the development of this learning model. This study was followed up with classroom action research to test the effectiveness of the learning model. The results showed that the greatest increase was in the cognitive domain, as well as student learning outcomes in football passing material above the minimum completeness value. These findings indicate that the learning model is proven to be effective in learning PJOK on football passing material for class VIII.